POLITENESS CONSTRUCTION IN MANGGARAI CULTURE: A STUDY ON THE LINGUISTIC ASPECT OF MANGGARAI LANGUAGE - Ignas Loy Semana (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Language is everything. Whatever people do in their daily life, when they come together, they use language. Language is tightly woven into human’s existence, that is, human is a thoughtful and ethical creation. In order to understand their humanity then we have to understand the language they use. Therefore, language is unique to human being because language it self can distinguish human from human, and human from animal. Human’s language is influenced by the social relationship between man and man. The construction of language chosen is indicated by the social status and the type of social relationship developed in the society. Conversely, the type of the social relationship and the social status are expressed in the construction of thechosenlanguage. The aim of the study, then, is to analyze and describe the construction of politeness developed in Manggarai society for the purpose of expressing the politeness in Manggarai culture. It is also to show the linguistic aspects developed in Manggarai language